FAKTOR YANG BERHUBUNGAN DENGAN PENOLAKAN KEIKUTSERTAAN PROGRAM VAKSINASI COVID-19 DI WILAYAH KERJA PUSKESMAS UNAAHA KABUPATEN KONAWE TAHUN 2021 - Dian Pratiwi; Hariati Lestari; Renni Meliahsari (Endemis Journal, 2022)
Indonesia is one of the countries in the world that is also experiencing the Covid-19 virus pandemic. The government has also taken countermeasures to prevent the transmission of the Covid-19 virus, namely by complying with health protocols and carrying out the Covid- 19 vaccination program which aims to reduce the transmission of Covid-19 and achieve herd immunity. The existence of the Covid-19 vaccination program has made the entire population of Indonesia raise various responses in the community. There is a lot of negative news about the Covid-19 vaccination program which makes people refuse to take part in the Covid-19 vaccination program. This refusal to participate in the Covid-19 vaccination program also occurred in the people of Konawe Regency. This is because there are people who easily accept hoax news, do not believe in the effectiveness of vaccines, and the lack of public knowledge that makes them afraid and hesitant to take part in the Covid-19 vaccination program. This study aims to determine the factors associated with the refusal to participate in the Covid-19 vaccination program in the work area of the Unaaha Health Center, Konawe Regency in 2021. This research method uses an analytical observational type of research with a cross sectional study approach and the sampling technique uses proportionate stratified random sampling. The results of the study concluded that there was a relationship between self-efficacy (p value = 0.000), public communication (p value = 0.001), and anxiety about side effects (p value = 0.004) with refusal to participate in the Covid-19 vaccination program.